Analisis Pengaruh Kompetensi Kepemimpinan terhadap Pengambilan Keputusan pada PT. Indomarco Prismatama Manado - Steifie Cornelisz; Sefanya Oratmangun; Inneke M. Makaliwe; Iskandar Rivai (CV. ALIM'SPUBLISHING, 2026)
Leadership is a key element in the smooth running of a company. Consequently, a leader’s competence will determine the direction the company takes. A competent leader is able to understand the situation and circumstances of the company they lead. They are also able to provide both guidance and motivation to those under their leadership. Furthermore, leadership competence will shape the decision-making process. The aim of this study is to determine the effect of leadership competence on decision-making at PT. Indomarco Prismatama Manado. The relevant research method employed was the correlational method, with a sample size of 50 participants selected using purposive sampling. The results of the data analysis indicate a functional relationship between the variable of organisational leadership competence and the variable of decision-making at PT Indomarco. In other words, the better a leader’s leadership competence, the greater the influence this will have on the decision-making process within the company. The functional relationship between the organisational leadership competence variable and the decision-making variable at PT Indomarco Prismatama Manado is positive. The correlation coefficient (r) is 0.687. The level of significance between the organisational leadership variable and the decision-making variable at PT Indomarco Prismatama Manado is quite significant. The determination of the organisational leadership competence variable on the decision-making variable at PT. Indomarco Prismatama Manado is quite significant at 0.471, or 47.10 per cent. This means that the leadership competence variable accounts for 47.10 per cent of the variation in decision-making. The remainder is influenced by other factors.